The Influence of Smartphone Use on the Social Life of Uninus Communication Studies Students Class A - Lisna Azka Nuraeni (Trigin Publisher, 2020)
This study aims to determine the extent of the influence of Smartphones on the social life of Uninus students of the Faculty of Communication Studies class A. The research method used is qualitative research using descriptive analysis techniques. The subjects studied were 27 respondents from class A who filled out the questionnaire data link that had been distributed by us as researchers. The data analysis of this research used descriptive analysis which resulted in the development of the theory of Media Equation Theory or media equation theory in which the Smartphone is the object of the research basis. By using the available Google Form access, as many as 27 respondents expressed various opinions after using a Smartphone. Starting from the duration used, what media platforms are accessed, to the influence felt in their social life. In the end, this research was able to justify and develop the theory of media equation theory.